2018
DOI: 10.1111/puar.12958
|View full text |Cite
|
Sign up to set email alerts
|

More than Pathological Formalization: Understanding Organizational Structure and Red Tape

Abstract: Evidence for Practice• Research suggests that red tape tends to correlate with organizational effectiveness and public service motivation, making red tape a matter of managerial concern.• When employees talk about red tape, they are referring to structural aspects of the workplace that are frustrating, including centralized decision making, tall hierarchies, and burdensome rules.• While red tape is subjective, public organizations should carefully evaluate rule effectiveness, consider pushing decision making d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 73 publications
1
31
0
1
Order By: Relevance
“…In their review of concepts and measures of red tape, Pandey and Scott (, 567) found agreement among scholars that “red tape is concerned with negative effects of rules and procedures.” Similarly, a survey among public sector employees found that when asked about their own definitions of red tape, participants most commonly referred to inefficient processes and barriers (Kaufmann, Borry, and DeHart‐Davis ). According to the most common definitions by Bozeman (, ), the distinction between necessary bureaucracy and dysfunctional red tape involves a normative judgment about a rule's contribution to a “legitimate” or “valued” purpose.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In their review of concepts and measures of red tape, Pandey and Scott (, 567) found agreement among scholars that “red tape is concerned with negative effects of rules and procedures.” Similarly, a survey among public sector employees found that when asked about their own definitions of red tape, participants most commonly referred to inefficient processes and barriers (Kaufmann, Borry, and DeHart‐Davis ). According to the most common definitions by Bozeman (, ), the distinction between necessary bureaucracy and dysfunctional red tape involves a normative judgment about a rule's contribution to a “legitimate” or “valued” purpose.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…There are several survey design suggestions which are recommended for addressing the potential of common source bias (Podsakoff, MacKenzie, & Podsakoff, 2012). Following two of these, items on the EECBG survey related to our substantive constructs were separated from each other, and the items related to different constructs used different response scales (Kaufmann, Borry, & DeHart-Davis, 2018). A third suggestion from Podsakoff et al (2012) is to collect data for dependent and independent measures from different sources.…”
Section: Methodsmentioning
confidence: 99%
“…The impacts of formalization are based on context and may be, positive, negative or neutral [17]. The organizational structure involves formalization, intricacy and close attention.…”
Section: Organizational Structurementioning
confidence: 99%